2015
DOI: 10.1159/000373961
|View full text |Cite
|
Sign up to set email alerts
|

AMH and AMHR2 Polymorphisms and AMH Serum Level Can Predict Assisted Reproduction Outcomes: A Cross-Sectional Study

Abstract: Background: In human assisted reproduction, the ovarian response to exogenous recombinant Follicle-stimulating Hormone (FSH) therapy is variable and difficult to predict. The standard protocol of ovarian hyperstimulation can result in satisfactory response; however, an unsatisfactory response necessitates FSH dose adjustment or results in ovarian hyperstimulation syndrome (OHSS). Polymorphisms in AMH and AMHR2 genes appear to affect hormone biological activities, thus affecting follicle recruitment and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 32 publications
0
40
3
2
Order By: Relevance
“…Overexpression of AMHR2 increases the binding of AMH to it, which attenuates follicular or oocyte maturation34. Therefore, AMHR2 is a possible indicator for the quality of embryo35. In PCOS oocytes, hormone receptors including LHCGR, FSHR, AMHR2, KAT2B, and OXTR were downregulated in the MII stage, which reflects the ability of oocyte to respond the higher hormone surge and protect the progress of oocyte mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of AMHR2 increases the binding of AMH to it, which attenuates follicular or oocyte maturation34. Therefore, AMHR2 is a possible indicator for the quality of embryo35. In PCOS oocytes, hormone receptors including LHCGR, FSHR, AMHR2, KAT2B, and OXTR were downregulated in the MII stage, which reflects the ability of oocyte to respond the higher hormone surge and protect the progress of oocyte mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited data on the role of hormonal in predicting OHSS, these markers have being increasingly utilized in predicting ovarian response to stimulation. AMH levels have been previously evaluated (23,24) and the results obtained presented much promise. A previous study demonstrated that AMH levels can identify women at high risk of developing OHSS (sensitivity 90.5%, specificity 81.3%), as a useful predictor of developing OHSS (12).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, clinical pregnancy was defined as the presence of an intrauterine gestational sac on the trans-vaginal ultrasound examination. We did not measure AMH concentrations [23][24][25].…”
Section: Discussionmentioning
confidence: 99%